Meshless modeling of bending behavior of bi-directional functionally graded beam structures. (15th December 2018) - Li, Jiao; Guan, Yanjin; Wang, Guangchun; Zhao, Guoqun; Lin, Jun; Naceur, Hakim; Coutellier, Daniel
Abstract: Bi-directional Functionally Graded Materials (FGMs) is of more and more focus in special engineering application like aerospace craft at high altitude and speed. In this paper, bending analysis of this type Functionally Graded Beam (FGB) is performed by a proposed meshless Total Lagrangian (TL) Corrective Smoothed Particle Method (CSPM) which owns more capability in accuracy and stability than the classical Smoothed Particle Hydrodynamics (SPH) method. This method is validated by comparison of the bending deformation with analytical method, ABAQUS and a self-programmed finite element code. The influence of the gradient indexes and boundary conditions on the deformation behavior is also investigated. The method is proved to be more precise and stable than the semi-analytical and FE results when dealing with power-law bi-directional FGB. Highlights: Meshless SPH method is developed for the bending analysis of two-directional Functionally Graded Beam (FGB). The convergence and accuracy of the proposed SPH model is validated by analyzing an exponentially varied bi-directional FGB. For bi-directional FGB of power-law model, the proposed SPH model is proved more precise than the semi-analytical solution in literature. The proposed SPH model shows better stability than FE solution by ABAQUS and a self-programmed code, where mesh is distorted.